Factors affecting private sector engagement in achieving universal health coverage: a scoping review - Naser Derakhshani; Ramin Rezapour; Saber Azami-Aghdash; Hamideh Nafar; Samira Soleimanpour; Emir Tahmazi Aghdam; Mohammadreza Maleki (Taylor & Francis Group, 2024)
Background Universal Health Coverage (UHC) is one of the most important strategies adopted by countries in achieving goals of sustainable development. To achieve UHC, the governments need the engagement of the private sector. Objective The aim of this study was to identify factors affecting private sector engagement in achieving universal health coverage. Methods The study is a scoping review that utilizes Arkesy & O'Malley frameworks. Data collection was conducted in MEDLINE, Web of Sciences, Embase, ProQuest, SID, and MagIran databases and the Google Scholar search engine. Also, manual searches of journals and websites, reference checks, and grey literature searches were done using specific keywords. To manage and screen the studies, EndNote X8 software was used. Data extraction and analysis was done by two members of the research team, independently and using content analysis. Results According to the results, 43 studies out of 588 studies were included. Most of the studies were international (18 studies). Extracted data were divided into four main categories: challenges, barriers, facilitators, goals, and reasons for engagement. After exclusion and integration of identified data, these categories were classified in the following manner: barriers and challenges with 59 items and in 13 categories, facilitators in 50 items and 9 categories, reasons with 30 items, and in 5 categories and goals with 24 items and 6 categories. Conclusion Utilizing the experience of different countries, challenges and barriers, facilitators, reasons, and goals were analyzed and classified. This investigation can be used to develop the engagement of the private sector and organizational synergy in achieving UHC by policymakers and planners.